A HELYIDENTITÁS FEJLESZTÉSE MESEPROJEKTTEL - Németh, Krisztina (Kultúratudományi Szemle, 2025)
Develop place-identity through folktale project The objective of the three-day storytelling project I devised was to enhance the student's comprehension of local history, thereby fostering their sense of place identity. My research aimed to assess the pupils' prior knowledge and the knowledge and experience they had acquired as a consequence of the project and to investigate potential changes in attitudes in this area. In the contemporary era, there is a growing tendency to overlook the significance of our sense of place-identity. However, I believe it is crucial to instil in our students a deep appreciation and respect for their environment from an early age to foster responsible and aware citizenship. My project was conducted at the Móra Ferenc Primary School in Mosonmagyaróvár, Hungary, under the title "Learning about our crafts through our folktales". The project focused on traditional local crafts and the surrounding villages, with an indirect approach based on the stories. This approach aimed to foster a deeper understanding of the natural wonders of Mosonmagyaróvár and the surrounding area rather than simply imparting new knowledge.